The Effect of Cooperative Learning on Reasoning Ability and Mastery of Mathematical Concepts - Agus Suyanto (STAI Miftahul Ula Nganjuk, 2021)
The purpose of this study was to determine the effect of learning methods on students' reasoning abilities and mastery of mathematical concepts. In this study, the authors used experimental research methods. Inferential analysis was performed using the Manova statistic (Multavariate Analysis of Arians). The results of the study concluded: (1) There was a significant effect of cooperative learning methods on reasoning abilities and mastery of mathematical concepts. This is evidenced by the value of Fo = 18, 154 and Sig = 0.000 <0.05. In this case, the reasoning ability and mastery of mathematical concepts in the experimental group was higher than the control group. (2) There is a significant effect of cooperative learning methods on mathematical reasoning abilities.˗value for the category of mathematical reasoning ability of 0.000 <0.05. Thus the null hypothesis is rejected or there is a significant difference between the mathematical reasoning ability of the group of students who were given the STAD type cooperative learning method and the mathematical reasoning ability of the group of students who were given the Jigsaw cooperative learning method. (3) There is a significant effect of the cooperative learning method. mastery of mathematical concepts. This is evidenced by the test results contained in the Test of Between table˗ Subject Effects in the statistical test above, it is known that the value of F = 29.894, p . value˗the value for the category of mastery of mathematical concepts is 0.000 < 0.05. Thus the null hypothesis is rejected or there is a significant difference between the mastery of mathematical concepts in the group of students who were given the STAD cooperative learning method and the mastery of mathematical concepts in the group of students who were given the Jigsaw cooperative learning method